Analysis Of The Implementation Of Web-Based Customer Relationship Management In Optimizing SME Services In Indonesia - Liana Trihardianingsih; Hanifah Permatasari (Proceeding of International Conference on Science, Health, And Technology, 2021)
Customer Relationship Management (CRM) is a fundamental and important business strategy for a company. Including one of them for Micro, Small and Medium Enterprises (SMEs) in Indonesia, which is increasingly active. The purpose of this study is to analyze the application of website-based CRM for SMEs in improving and helping service optimization. Optimization of this service discount sense that a company can not only optimize when a business process is going, but also how the service can continue to operate optimally after all transactions have been resolved. The study used a qualitative descriptive analysis that relied on sources from literature studies. Several scientific articles discussing the application of CRM in the Indonesian SME sector have been collected for analysis. It is used to discover usage facts, the modules used, and how SMEs can maximize services using the tools. Results from this study is there some CRM services are popular among SMEs and always to continue optimized functionality. This is supported CRM capabilities in facilitating the interaction between consumers and businesses when the business process occurs. All information, data, and services can be processed more easily and quickly with based websites. The existence of this web based CRM makes SMEs can improve the services provided which have an impact on customer satisfaction and loyalty efficiently.